FOXM1D potentiates PKM2‐mediated tumor glycolysis and angiogenesis. Issue 5 (2nd April 2021) - Zhang, Wei; Zhang, Xin; Huang, Sheng; Chen, Jianfeng; Ding, Peipei; Wang, Qi; Li, Luying; Lv, Xinyue; Li, Ling; Zhang, Pingzhao; Zhou, Danlei; Wen, Wenyu; et al.
Abstract : Tumor growth, especially in the late stage, requires adequate nutrients and rich vasculature, in which PKM2 plays a convergent role. It has been reported that PKM2, together with FOXM1D, is upregulated in late‐stage colorectal cancer and associated with metastasis; however, their underlying mechanism for promoting tumor progression remains elusive. Herein, we revealed that FOXM1D potentiates PKM2‐mediated glycolysis and angiogenesis through multiple protein–protein interactions. In the presence of FBP, FOXM1D binds to tetrameric PKM2 and assembles a heterooctamer, restraining PKM2 metabolic activity by about a half and thereby promoting aerobic glycolysis. Furthermore, FOXM1D interacts with PKM2 and NF‐κB and induces their nuclear translocation with the assistance of the nuclear transporter importin 4. Once in the nucleus, PKM2 and NF‐κB complexes subsequently augment VEGFA transcription. The increased VEGFA is secreted extracellularly via exosomes, an event potentiated by the interaction of FOXM1 with VPS11, eventually promoting tumor angiogenesis. Based on these findings, our study provides another insight into the role of PKM2 in the regulation of glycolysis and angiogenesis. Abstract : FOXM1D binds to tetrameric PKM2 and assembles a heterooctamer, thereby promoting aerobic glycolysis. Further, FOXM1D interacts with PKM2 and NF‐κB and induces their nuclear translocation via importin 4. The nuclear PKM2 and NF‐κB complexes subsequently augment VEGFA transcription. The increased VEGFA is secreted extracellularly via exosomes, an event potentiated by the interaction of FOXM1 with VPS11, eventually promoting tumor angiogenesis.